Nickel-based nitrodopamine MOF and its derived composites functionalized with multi-walled carbon nanotubes for efficient OER applications. (1st January 2023) - Kiran, Sonia; Yasmeen, Ghazala; Shafiq, Zahid; Abbas, Amir; Manzoor, Sumaira; Hussain, Dilshad; Adel Pashameah, Rami; Alzahrani, Eman; Alanazi, Abdullah K.; Naeem Ashiq, Muhammad
Graphical abstract: Highlights: Ni based MOF composites were solvothermally synthesized with multi-walled carbon nanotubes with enhanced surface area. Ni-nitrodopamine (NDA/MWCNTs-a) electrocatalyst exhibits outstanding catalytic activity for OER. Electrocatalyst has overpotential of 285 mV to attain current density of 10 mA cm −2 for OER. Chronoamperometric analysis were made for estimation of long-term stability of electrocatalyst for 24 h. Abstract: In recent era, development of an un-expensive, highly effective, green and robust electrocatalyst for the production of hydrogen via water splitting is a major consequence to deal with energy crisis. In the present work, a novel Ni based MOF and its nanocomposite functionalized with multi-walled carbon nanotubes (MWCNTs) is synthesized via solvothermal method. To increase the catalytic activity of the synthesized material, heat treatment of the fabricated MOF is carried out at 673 K for 3 h. For structural, textural and morphological studies different analytical techniques are applied with subsequent utilization of synthesized materials for catalyzing slow oxygen evolution reaction (OER). Amongst all Ni-nitrodopamine (NDA/MWCNTs-a) electrocatalyst displays outstanding catalytic activity at low overpotential of 285 mV, small Tafel slope of 73 mV dec -1, and long-term stability of 24 h surpassing the catalytic proficiency for noble metal oxides such as IrO2 and RuO2 .